Hubungan Komunikasi Terapeutik Perawat Terhadap Tingkat Kecemasan Pasien di Unit Gawat Darurat - Deswita, Reny; Perdani, Zulia Putri; Nuraini; Juniarto, Rachmat (PT. Pubsains Nur Cendekia, 2025)
Background: The Emergency Unit is the starting point for emergency patients who need first aid. Entering the emergency room can cause anxiety in patients. The anxiety felt by patients can worsen the patient's condition while the patient is receiving treatment. Aims: To identify the relationship between nurses' therapeutic communication and patient anxiety levels in the emergency room. Method: Quantitative research design with a cross-sectional approach, as many as 40 respondents through purposive sampling, anxiety level questionnaire using the Depression, Anxiety and Stress Scale - 21 (DASS-21). Data analysis using Spearman Rank correlation. Result: The majority of respondents had mild anxiety as many as 13 people (32.5%). There is a significant relationship between nurses' therapeutic communication and patient anxiety levels (p value <0.005), with a correlation coefficient of -0.975. This value shows a very strong and negative relationship between therapeutic communication and anxiety levels. the better the therapeutic communication provided by nurses, the lower the patient's anxiety level tends to be. Discussion: Therapeutic communication by nurses plays an important role in reducing patient anxiety. Empathetic, clear, and supportive communication can help patients feel calmer and safer in emergency situations. Therapeutic communication training for nurses in the ER needs to be improved as part of efforts to improve the quality of care and patient comfort.